Influence of Cationic Surfactants on the Formation and Surface Oxidation States of Gold Nanoparticles Produced via Laser Ablation - Fong, Yuen-Yan; Gascooke, Jason; Visser, Bradley; Harris, Hugh; Cowie, Bruce; Thomsen, Lars; Metha, Gregory; Buntine, Mark (American Chemical Society, 2013)
We report on the time evolution of gold nanoparticles produced by laser ablation in the presence of the cationic surfactants cetyltrimethylammonium bromide (CTAB) and cetyltrimethylammonium chloride (CTAC) in aqueous solution. The broader applicability of a laser-inducednanoparticle formation kinetic model previously developed by us for the case of anionic surfactants in aqueous solution [J.Pys. Chem. C 2010, 114, 15931-15940] is shown to also apply in the presence of cationic surfactants. We explore the surface properties of the nanoparticles produced in thepresence of the cationic surfactants via synchrotron X-ray photoelectron spectroscopy (XPS). The XPS data indicate that at CTA+ concentrations approximating the aqueous criticalmicelle concentration AuIII is present on the nanoparticle surface. Such oxidation is not observed at (i) lower CTA+ concentrations, (ii) in the presence of an anionic surfactant, or (iii) in the case of pure water as a solvent.